Safety of Long Acting Reversible Contraception (LARC) during 3 Months of Follow up At Civil Hospital, Karachi: Safety of Long Acting Reversible Contraception - Tariq, Sidra; Farhan, Anum; Tasneem, Maria; Meer, Sumaira; Khan, Daniya; Sabir, Sadaf (Pakistan Journal of Health Sciences, 2024)
Contraception counseling is an essential component of family planning services. It provides the foundation for delivering correct information on contraceptive methods and eliminating myths regarding risks and negative effects. Objectives: To determine the Safety of Long-Acting Reversible Contraception (LARC) for postpartum contraception during 3 months of follow-up. Methods: A cross sectional descriptive study comprised on total of 108 women aged 25-35 years who accepted LARC in the postpartum period at Department of Obstetrics and Gynaecology, Civil Hospital, Karachi from 22nd February 2021 to 21st August 2021, were included. Females with uterine abnormalities and severe anemia were excluded. The demographic information (name, age, registration number) was taken. The women were counseled regarding postpartum contraception LARC such as IUD or Jedelle (implant) during the antenatal period and LARC was placed within 30 minutes of placental delivery. Those women who selected LARC were called for follow-up for 3 months in OPD and at follow-up visits, patients were assessed for their safety of this method. Results: The age range in this study was from 25 to 35 years with a mean age of 28.81 ± 3.27 years. The majority of the patients 80 (74.07%) were between 25 to 30 years of age. The mean parity was 3.10 ± 0.72. In this study, the safety of Long Acting Reversible Contraception (LARC) for postpartum contraception during 3 months of follow-up was found in 91 (84.26%) women. Conclusions: This study concluded that long acting reversible contraceptives in the immediate postpartum period are very safe.